(untitled) (One Health & Risk Management, 2022)
The Journal , One Health&Risk Management’’ funded in 2019 by Moldavian Biosafety and Biosecurity Association disseminates important and valuable results of scientific researches from different disciplines under the umbrella , One Health’’ which promotes a better world and better public health.